Plan de Mejoramiento en el Modelo de Gestión del Talento Humano para el Programa de Tutorías para el Aprendizaje en la ciudad de Medellín. - Berrio Soto, Gabriel Jaime; Florez Vásquez, Jorge Antonio (Universidad Antonio Nariño, 2025)
This study aims to design an improvement plan for the human talent management model of the "Tutoring Program for Learning" (PTA) within the Secretariat of Educacion of the city of Medellín. Through a general diagnosis of the current functioning of the program in terms of administrative management, key aspects that require adjustments to optimize its operation were identified. The research includes the identification of specific actions that will strengthen human talent management and, finally, the development of a concrete improvement plan proposal